POTENSI OBJEK WISATA TORAJA UTARA BERBASIS KEARIFAN LOKAL SEBAGAI SUMBER MATERI GEOGRAFI PARIWISATA - Masri Ridwan; Ach. Fatchan; I Komang Astina (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
This research focused on the tourism potential of North Toraja based on local wisdom. The method of this study implemented qualitative using ethnography approach. The results showed that (1) the tourism objects in North Toraja are potential in the aspect of culture, nature and history (2) the tourism areas in North Toraja must be under supervised and controlled by Foundations, Farmers, Local Government, and family. (3) Development of tourism objects in the basis of local wisdom supports the continuation of tourism in North Toraja. (4) Tourism in North Toraja based on local wisdom can be used as a source of learning materials for Tourism Geography courses in the Department of Geography, State University of Makassar. The implication of this study will be used a source of support materials Tourism Geography subjects particularly in Tourism Potential Local Content.Penelitian tentang potensi obyek wisata Toraja Utara berbasis kearifan lokal. Hasil dari penelitian digunakan sebagai sumber materi pendukung matakuliah Geografi Pariwisata. Penelitian ini menggunakan pendekatan kualitatif, bertujuan menghasilkan laporan etnografi. Hasil penelitian adalah (1) kawasan obyek wisata Toraja Utara memiliki potensi wisata budaya, alam dan sejarah (2) Pengelola kawasan wisata Toraja Utara diantaranya: Yayasan, Petani, Pemda, dan Keluarga. (3) Pengembangan Objek wisata berbasis kearifan lokal setempat mendukung kelangsungan wisata di Toraja Utara. (4)  Wisata Toraja Utara berbasis kearifan lokal dapat digunakan sebagai sumber materi belajar M.k Geografi Pariwisata Jurusan Geografi FMIPA Universitas Negeri Makassar yakni Materi Potensi Wisata lokal.